A fasting period during grow-out make juvenile pacu (Piaractus mesopotamicus) leaner but does not impair growth - Favero, GiseleCristina [UNESP]; Gimbo, Rodrigo Yukihiro [UNESP]; Montoya, Luz Natália Franco [UNESP]; Carneiro, Dalton José [UNESP]; Urbinati, Elisabeth Criscuolo [UNESP] (Elsevier, 2020)
We evaluated the effect of a 30-day fast followed by 30 days of feeding on the dynamics of energy mobilization and the growth performance in juvenile pacu (Piaractus mesopotamicus). Pacu is a freshwater fish known for its high amount of body fat, an undesirable marketing trait. This study was conducted to determine whether a fasting strategy could reduce fat stores without impairing fish growth. For that, a total of 300 juvenile fish (41.5 ± 12.9 g) were distributed into 12 tanks (six tanks per experimental group), and sorted in two feeding strategies: continuous feeding during 60 days (control group) and 30 days of fasting followed by 30 days of refeeding (30/30 group). Growth, nutritional and biometric parameters were evaluated: final weight, weight gain, specific growth rate (SGR), feed conversion ratio, protein efficiency rate, feed intake, hepatosomatic index (HSI) and mesenteric fat index (MFI). Also tissues metabolic indicators were assayed in liver (lipids and glycogen) and muscle (lipids and protein) as well as blood metabolites (glucose, triglycerides, cholesterol, non-esterified fatty acids (NEFA) and total serum protein). After experimental time the results displayed that, fasting period of 30 days decreased the glucose and triglycerides and increased the serum cholesterol and NEFA concentrations. In liver, fasting reduced glycogen and total lipid concentrations, as well as the HSI. Total lipid in muscle and in viscera (MFI) also reduced along the fasting and remained lower than in control during the refeeding. The refeeding promoted hyperphagia and full growth compensation in fasted fish, which reached similar weight gain and specific growth rate to those of continuously fed fish. The long-term fasting in pacu may favour the production of a leaner fish, without compromising its growth, and additionally reduce feeding cost.
Keywords: Compensatory growth; Energetic metabolism; Food deprivation; Hyperphagia